Preparation and Characterization of Impregnated Commercial Rice Husks Activated Carbon with Piperazine for Carbon Dioxide (CO2) Capture - Siti Noraishah, Masoum Raman; Nur Aminatulmimi, Ismail; Saidatul Shima, Jamari (2016)
Development of effective materials for carbon dioxide (CO2) capture technology is a fundamental importance to reduce CO2 emissions. This work establishes the addition of amine functional group on the surface of activated carbon to further improve the adsorption capacity of CO2. Rice husks activated carbon were modified using wet impregnation method by introducing piperazine onto the activated carbon surfaces at different concentrations and mixture ratios. These modified activated carbons were characterized by using X-Ray Diffraction (XRD), Brunauer, Emmett and Teller (BET), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). The results from XRD analysis show the presence of polyethylene butane at diffraction angles of 21.8° and 36.2° for modified activated carbon with increasing intensity corresponding to increase in piperazine concentration. BET results found the surface area and pore volume of non-impregnated activated carbon to be 126.69 m2/g and 0.081 cm3/g respectively, while the modified activated carbons with 4M of piperazine have lower surface area and pore volume which is 6.77 m2 /g and 0.015 cm3/g respectively. At 10M concentration, the surface area and pore volume are the lowest which is 4.48 m2/g and 0.0065 cm3/g respectively. These results indicate the piperazine being filled inside the activated carbon pores thus, lowering the surface area and pore volume of the activated carbon. From the FTIR analysis, the presence of peaks at 3312 cm-1 and 1636 cm-1 proved the existence of reaction between carboxyl groups on the activated carbon surfaces with piperazine. The surface morphology of activated carbon can be clearly seen through FESEM analysis. The modified activated carbon contains fewer pores than non-modified activated carbon as the pores have been covered with piperazine